PENGARUH PHYSICAL ENVIRONMENT TERHADAP EXPERIENCE VALUE TAMU HOMESTAY DI DESA WISATA LAWANG KABUPATEN AGAM - Umayra, Nurul Aisha; Wulandari, Dwi Pratiwi (Ensiklopedia of Journal, 2025)
So, This research done because there are some problem regarding Experience Value in homestays in Desa Wisata Lawang Kabupaten Agam. The aim of this research is to analyze the influence of the Physical Environment regarding the Experience Value of homestay guests in Desa Wisata Lawang. The method of this research used is descriptive quantitative and causal associative. The sampling technique used is incidental sampling technique. Quantitative Analysis using Simple Linear Regression. The research results show that there is an influence of the Physical Environment on the Experience Value of Homestay Guests in Desa Wisata Lawang. The novelty of this research  is revealed that tourist or guest need when they choose to stay in a homestay of a tourism village is their experience regarding physical environment. This is refers to Layout Accessibility, Facility Aesthetics, Seating Comfort, Electonic Equipment, and Facility Cleanliness. So, although a homestay always serve the guest with local wisdom condition, we can not denied that they still need and influence by Physical Environment to optimized Experience Value. Keywords: physical environment, experience value, homestay